The status quo of short video as sources of health information on gastroesophageal reflux disease in China: a cross-sectional study - Cai, Ying; Zeng, Hao; Yang, Pingping; Xu, Xiwen; Lai, Yongkang; Zhou, Yu (Frontiers in Public Health, 2024)
Background Positive lifestyle adjustments have become effective methods in treating gastroesophageal reflux disease (GERD). Utilizing short video platforms to encourage GERD patients for effective self-disease management is a convenient and cost-effective approach. However, the quality of GERD-related videos on short video platforms is yet to be determined, and these videos may contain misinformation that patients cannot recognize. This study aims to assess the information quality of GERD-related short videos on TikTok and Bilibili in China. Methods Search and filter the top 100 GERD-related videos on TikTok and Bilibili based on comprehensive rankings. Two independent gastroenterologists conducted a comprehensive evaluation of the video quality using the Global Quality Score and the modified DISCERN tool. Simultaneously, the content of the videos was analyzed across six aspects: definition, symptoms, risk factors, diagnosis, treatment, and outcomes. Results A total of 164 GERD-related videos were collected in this study, and videos from non-gastrointestinal health professionals constitute the majority (56.71%), with only 28.66% originating from gastroenterology health professionals. The overall quality and reliability of the videos were relatively low, with DISCERN and GQS scores of 2 (IQR: 2–3) and 3 (IQR: 2–3), respectively. Relatively speaking, videos from gastrointestinal health professionals exhibit the highest reliability and quality, with DISCERN scores of 3 (IQR: 3–4) and GQS scores of 3 (IQR: 3–4), respectively. Conclusion Overall, the information content and quality of GERD-related videos still need improvement. In the future, health professionals are required to provide high-quality videos to facilitate effective self-disease management for GERD patients.